Education in the Arts: Debate Between the Term Artist or Teacher - Velázquez Hernández, Jorge Arturo; Romero Zepeda, Jorge Adán; Alonso Chombo, Rosalía; Ordaz Mejía, María Nallely (Archives of Business Research, 2022)
The arts today have gained a lot of strength because it has been believed that they help improve student performance, favor education and learning, managing to lead the learner to the generation of significant knowledge. In this sense, this research aims to elucidate the impact and importance between the terms of artist and the figure of the art teacher. It seeks to express that both terms are related to education and the development of student learning. The results obtained will seek to make a proposal in which, based on what has been analyzed and referenced, the work of an art teacher within the school field can be defined, in addition to his artistic vocation that is completely balanced with his teaching vocation.